Comparison of Intercuneiform 1-2 Joint Mobility Between Hallux Valgus and Normal Feet Using Weightbearing Computed Tomography and 3-Dimensional Analysis. (March 2018) - Kimura, Tadashi; Kubota, Makoto; Suzuki, Naoki; Hattori, Asaki; Marumo, Keishi
Background: An association has been reported between hallux valgus and hypermobility of the first ray, but subluxation of the intercuneiform 1-2 joint was also suspected in some cases. However, dynamics of the intercuneiform 1-2 joint has seldom been investigated. This study used weightbearing computed tomography (CT) and a 3-dimensional (3D) analysis system to evaluate displacement of the intercuneiform 1-2 joint, intercuneiform 2-3 joint, and second cuneonavicular joint due to weightbearing in hallux valgus and normal feet. Methods: Patients were 11 women with hallux valgus (mean age, 56 years; mean hallux valgus angle, 43 degrees; mean first-second intermetatarsal angle, 22 degrees) and 11 women with normal feet (mean age, 57 years; mean hallux valgus angle, 14 degrees; mean first-second intermetatarsal angle, 9 degrees). Each patient was placed supine with the lower limbs extended, and CT was performed under nonweightbearing and weightbearing conditions (load equivalent to body weight). 3D models reconstructed from CT images were used to compare displacement of the intermediate cuneiform relative to the medial cuneiform under nonweightbearing and weightbearing conditions. Results: Relative to the medial cuneiform, the middle cuneiform was displaced by 0.1 and 0.8 degrees due to dorsiflexion, 0.2 and 1.0 degrees due to inversion, and 0.7 and 0.7 degrees due to abduction in normal feet and feet with hallux valgus, respectively, with the latter having significantly greater dorsiflexion ( P = .0067) and inversion ( P = .0019). There was no significant intergroup difference at the intercuneiform 2-3 joint and second cuneonavicular joint. Conclusion: This study clarified the detailed load-induced displacement of the cuneiform 3-dimensionally. Compared with normal feet, hallux valgus feet had significantly greater mobility of the intercuneiform 1-2 joint, suggesting hypermobility of this joint. Level of Evidence: Level III, case-control study.